Levantamento bibliográfico do comportamento informacional de mulheres adultas para investigação de autismo - Botiglieri, Julia Beatriz (Universidade Federal de São Carlos, 2023)
Women within the ASD - autistic spectrum disorder - still depend heavily on their own hypotheses and research to actually discover themselves as an autistic woman. All the characteristics that differentiate them from male individuals within the spectrum, added to studies historically focused on more apparent characteristics, involuntarily promote the self-diagnosis of these girls and women. For self-diagnosis to occur and even for the hypothesis of autism to arise, it is necessary that the subject in question first emerges with an informational need. From this movement, Informational Behavior is born, which is understood to be responsible for these women to have concrete conclusions about their own mental health. Thus, the present study was carried out with the main objective of examining the existing studies that addressed the issue of Informational Behavior of adult women for self-diagnosis in autism. For that, searches were carried out in three databases with different scopes, namely the Web of Science, PubMed and Brapci. Such searches were carried out with a focus on the expression assembly strategy, with the intention of elaborating a search script capable of demonstrating the hypothesis of this research: that this is a subject that is not yet being addressed by information scientists and other professionals. Through the searches, the initial hypothesis of this research was proven and the existing gap in the literature was highlighted. The main results showed returns focused on autism in general and, sometimes, the informational behavior of parents of autistic children, but never all essential aspects for the research question. In this way, it was concluded that this really is a fertile field for research, mainly in the field of Informational Behavior, in particular due to the social role to be played by librarians and information scientists contributing positively to social well-being.
Bibliographic survey of the information behaviour of adult women for the investigation of autism
Keywords: Autismo; Autism; Mulheres; Women; Comportamento informacional; Information behaviour; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO